Third Cycle of General Basic and Diversified Academic Costa Rican Education: A Comparative Analysis of their Curricular Structures from the Viewpoint of Inclusion, Exclusion, and Educational Inequality - Seravalli Monge, Giannina (2023)
Within the framework of the research activity carried out from the program Profiles, Dynamics and Challenges of Costa Rican Education from CIDE, Universidad Nacional, Costa Rica, a comparative study was conducted among the different socio-educational factors and inclusion-exclusion actions present in the secondary educational level at a national scope. As a result, a description of the conformation of the public education system was made and the study plans are analyzed taking as a reference the provisions of the Ministry of Public Education and in the document called Compendium of Offers and Services of the Costa Rican Educational System 2016. For the analysis, an assessment of the curricular characteristics was carried out, in terms of subjects and number of lessons, of each curricular plan and the description of each of them was compared using the study plan of traditional academic schools as a point of reference. The main goal of doing this analysis was to identify whether the different curricular proposals could generate inclusion, exclusion, and educational inequality from the student training processes on the Costa Rican public education subject curricula.